2022
DOI: 10.3390/ijms24010680
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Eribulin Plus Gemcitabine Combination in L-Sarcomas

Abstract: Although the overall survival of advanced soft-tissue sarcoma (STS) patients has increased in recent years, the median progression-free survival is lower than 5 months, meaning that there is an unmet need in this population. Among second-line treatments for advanced STS, eribulin is an anti-microtubule agent that has been approved for liposarcoma. Here, we tested the combination of eribulin with gemcitabine in preclinical models of L-sarcoma. The effect in cell viability was measured by MTS and clonogenic assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…It was approved in the United States in 2010 for the second-line treatment of metastatic breast cancer and in 2016 for liposarcoma. The cell cycle-dependent MOA and good safety record make eribulin an ideal partner for systemic therapies, such as anti-angiogenesis TKI (levantinib 20 ) or gemcitabine 21 for liposarcoma and leiomyosarcoma or immune checkpoint inhibitors for urothelial carcinoma 22 and breast cancer 23 . Eribulin has usually been given at a dose of 1.4 mg/m 2 IV on days 1 and 8 of a 21-day cycle, the recommended dose for monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…It was approved in the United States in 2010 for the second-line treatment of metastatic breast cancer and in 2016 for liposarcoma. The cell cycle-dependent MOA and good safety record make eribulin an ideal partner for systemic therapies, such as anti-angiogenesis TKI (levantinib 20 ) or gemcitabine 21 for liposarcoma and leiomyosarcoma or immune checkpoint inhibitors for urothelial carcinoma 22 and breast cancer 23 . Eribulin has usually been given at a dose of 1.4 mg/m 2 IV on days 1 and 8 of a 21-day cycle, the recommended dose for monotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of gemcitabine in combination with other drugs for STSs is inferior to that of docetaxel plus gemcitabine ( Table 5 ). In addition, gemcitabine in combination with emerging drugs, such as pazopanib and eribulin, has also been tested for the treatment of STSs ( Somaiah et al, 2021 ; Lopez-Alvarez et al, 2022 ). In summary, gemcitabine and docetaxel have similar efficacy and status in the treatment of STSs.…”
Section: Efficacy Of Different Drugs In Stssmentioning
confidence: 99%
“…Among the new anticancer drugs, eribulin, an anti-microtubule agent, has demonstrated antitumour effects in patients with L-sarcoma. In this Special Issue, López-Álvarez et al demonstrated the efficacy of eribulin combined with gemcitabine in preclinical models of L-sarcoma [ 7 ]. In L-sarcoma cell lines, the combination of eribulin and gemcitabine was shown to have synergistic effects, increasing the number of hypodiploid events and the accumulation of DNA damage.…”
mentioning
confidence: 99%